Leśnicy w Armii gen. Andersa. Komentarz do materiałów przechowywanych w Instytucie Hoovera - Kosel, Bogusław (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2018)
During the Soviet occupation of Polish eastern borderlands in 1939–1941 thousands of foresters were arrested and deported to distant regions of Soviet Union. They were forced to work and live in poor conditions. After German invasion on Soviet Union, foresters such as Polish citizens were granted amnesty, which gave them possibility to move from prisons and labor camps. Some of them decided to join Polish Millitary Forces formed on Soviet teritory. The aim of the Oki article is to review documents from archive of Hoover Institution related to Polish foresters serving in Anders Army. Paper consist of analytical part and annex enlisting more than 350 names of soldiers. List additionally contains data of foresters who left their memoires about their stay in Soviet Union.